A A STUDY OF LISTENING COMPREHENSION PROBLEMS ENCOUNTERED BY THE THIRD SEMESTER STUDENTS AT STMIK PRABUMULIH - Hepnyi Samosir (Universitas Muhammadiyah Kalimantan Timur, 2019)
Even though listening is often categorized as a passive activity, it is not a simple process as it may seem. There is an active process because in it. Listeners must focus on the spoken language and actively draw what message is being delivered. There are some factors that make a listener may need a lot of work to comprehend a spoken language such as colloquialism, accent, intonation, hesitation, word or phrase clusters, and content. Preliminary data gained from pre-observation at STMIK Prabumulih showed that the third semester students found themselves hard to acquire information from spoken language, hence it is necessary to find out the causes so that make an effort to develop their listening skills. The method used is descriptive research design. The result reveals that students encounter various kinds of listening problems in learning comprehension such as unfamiliar words, the length and of the spoken text, speed rate, lack of concentration and pronunciation, and the noises around come from both the background sound of the spoken language recording and environmental sound such as sound from outside classroom. Keywords: listening; comprehension; listening comprehension problems; descriptive